2022
DOI: 10.1097/nmc.0000000000000803
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Control Trial to Assess the Impact of Lavender on Anxiety and Comfort After Cesarean Birth and the Barriers Encountered

Abstract: This study aimed to assess the effect of lavender aromatherapy on anxiety and comfort after cesarean birth. Study Design: Randomized control trial. Methods: Forty-eight patients who had a cesarean birth were asked to complete the six-item State and Trait Anxiety (STAI-6) score to assess their level of anxiety pre-and postapplication of either lavender aromatherapy or placebo during their inpatient postpartum stay. Their comfort and pain levels pre-and postadministration were assessed, and differences between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the present study, postprocedural comfort levels were significantly higher in the experimental group than in the control group. Previous studies have also reported that lavender oil increased patient comfort (Burgess, Harris, & Wheeling, 2022; Kasar et al, 2020; Ozen et al, 2022). Our finding is thus consistent with the current literature.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, postprocedural comfort levels were significantly higher in the experimental group than in the control group. Previous studies have also reported that lavender oil increased patient comfort (Burgess, Harris, & Wheeling, 2022; Kasar et al, 2020; Ozen et al, 2022). Our finding is thus consistent with the current literature.…”
Section: Discussionmentioning
confidence: 91%